Psychological Well-Being and Intrinsic Motivation: Relationship in Students Who Begin University Studies at the School of Education in Ciudad Real - González Olivares, Ángel Luis; Navarro, Óscar; Sánchez-Verdejo, Francisco Javier; Muelas, Álvaro (Frontiers in Psychology, 2020)
More and more studies and research have found a positive relationship between the participation of young peoplein altruistic activities and helping others. It is interesting to discover the relationship that personal and vocational satisfaction play in the preparation and training for the teaching profession. For students who begin university studies related to teaching, their psychological well-being and motivation toward this activity are very relevant aspects to consider. The access to and attainment of a university degree with a great vocational character, such as that of Pre-school Teacher or Primary Education Teacher, can benefit the students under their tutelage. An adequate motivation and a psychological well-being might favor future educational professionals’ personal balance and will impact their students. This research aims to analyze the degree of psychological well-being and its relationship with the motivation toward starting the teaching career. A sample of 233 students and students aged between 17 and 19 who are beginning university studies at the School of Education of Ciudad Real was selected. All participants were enrolled in the first year of the Degree in Pre-school and Primary Education. The relationship between the psychological well-being of the students and their motivation toward attaining a professional teaching career was analyzed. Other variables, such as age or gender were also taken into account. A quantitative study was carried out and the Ryff Psychological Well-Being Scale (RPWS) and the validated Intrinsic Motivation Questionnaire (IMI) were used. Once the results were analyzed, it was observed that there is a positive correlation between the perception of psychological well-being that the participants have and their motivation toward the beginning of university studies. The focal point of these future teachers is direct teaching with the students of the early stages of Pre-school and Primary Education. There are also some significant differences, considering the age and gender of the participants. The vocational character of university preparation for the teaching profession may determine that students who begin their degree studies have an important motivation toward the performance of their professional future.